Delayed Commissuroplasty Increases Interincisal Distance in Buccogingival Cancer Patients Treated with Free Flap Reconstruction of the Oral Commissure - Hung, Shao Yu; Hanba, Curtis; Chang, Tommy Nai-Jen; Chen, Yan-Lin; Lu, Johnny Chuieng-Yi (Journal of Reconstructive Microsurgery, 2024)
Background Oral cavity cancers requiring excision of the oral commissure and free flap reconstruction often requires commissuroplasty to manage oral incontinence. We aimed to evaluate the implications of primary versus delayed commissuroplasty on drooling, and interincisal distance outcomes in this cohort.Methods A retrospective query of head and neck cancer patients operated by a single surgeon from 2017 to 2020 was performed. Patients were included if they underwent free flap reconstruction of the oral commissure, had an immediate or delayed commissuroplasty, and had 2 years of follow-up data including Thomas-Stonell and Greenberg drooling rating scales and interincisal distance measurements.Results Thirty-five patients were included in the review. Twelve patients received immediate commissuroplasty and 23 patients had delayed commissuroplasty. Interincisal distance was similar at baseline, although significantly varied between immediate and delayed commissuroplasty groups at 1 month and 2 years postoperative. Drooling scores were significantly elevated in the group treated with delayed commissuroplasty, but eventually normalized after staged surgery and follow-up. Patients treated with adjunct radiation therapy had lower interincisal distance than patients who did not have radiation.Conclusion Delayed commissuroplasty increased interincisal distance and normalize drooling in patients who required full-thickness excision of the buccal mucosa and oral commissure and free tissue reconstruction. The presented data can help to educate patients on expected postoperative outcomes and likely advocates for a second-stage procedure after completion of adjunct radiotherapy to achieve optimal commissural placement and oral competence.
Keywords: interincisal distance; commissuroplasty; oral cavity reconstruction; free flap